Microbial community transfers across a pilot ripening cellar are increased by cheese wiping - Reshad Fantelli; Patricia Battais; Sébastien Theil; Elisa Michel; Mathilde Lacalmontie; Sandrine Jacquenet; Sullivan Lechêne; Christophe Chassard; Philippe Duquenne; Céline Delbès (Food Microbiology, 2026)

Bidirectional associations between biological aging, cardiovascular health, and cardiovascular risk: findings from the INSPIRE-T lifespan cohort - Mathilde Strumia; Vanina Bongard; Samuel Thuriot; Philippe Cestac; Brigitte Sallerin; Jean-Marc Lemaitre; David Furman; Sophie Guyonnet; Bruno Vellas; Sandrine Andrieu; Laure Rouch; Sophie Guyonnet; et al. (GeroScience, 2026)
Chronological age is a common and non-modifiable factor for chronic disease, but does not fully explain age-related changes. Biological clocks have been developed to explore biological aging mechanisms. They could help identify protective factors against accelerated aging and associated diseases. We aim to assess the association between reduced epigenetic or inflammatory aging and ideal cardiovascular health or cardiovascular risk. We conducted a cross-sectional analysis of participants from the INSPIRE-T cohort. Cardiovascular health (CVH) was assessed using the Life’s Essential 8 score. Cardiovascular risk was assessed using the American Framingham risk score (FRS) and the European Systematic Coronary Risk Evaluation (SCORE2) score. Epigenetic and inflammatory aging was calculated from the residuals from linear regression of biological age (based on five epigenetic clocks and one inflammatory clock) and chronological age. Linear and logistic regression models were used. Better CVH has been associated with slower epigenetic aging, particularly in younger subjects and men. Accelerated epigenetic aging measured by GrimAge was associated with an increase cardiovascular risk (for SCORE2: OR = 1.10 95%CI [1.04; 1.16]). No persistent association was found with the inflammatory clock. Our study reported an association between ideal global CVH with reduced epigenetic aging after adjustment for chronological age and gender. This suggests that epigenetic aging may be modifiable through healthy lifestyle and cardiovascular risk management, although a potential underlying causal relationship remains to be established. Moreover, accelerated epigenetic aging is linked to worsening cardiovascular risk, and could be a new risk factor alongside chronological age. Graphical Abstract

Space density affects resting location and proximity of fattening pigs at night - Mathilde Coutant; Juliette Michel; Lene J. Pedersen; Mona L.V. Larsen (Livestock Science, 2026)

The phytochemical diversity of wild hops from northern France for potential brewing application - Augustin Bildstein; Mathilde Vandenberghe; Anne-Sophie Paguet; Gabriel Lefèvre; Louis Raymond; Gaëtan Kientz; Jennifer Samaillie; Franck Michels; Séverine Derbré; Cécile Palaric; David Mathiron; Marie-Laure Fauconnier; et al. (Phytochemistry Letters, 2025)

ALBATROSS: Advancing Southern Ocean tide modelling with high resolution and enhanced bathymetry - Eva Le Merle; Carole Belot; Ergane Fouchet; Mathilde Cancet; Ole Baltazar Andersen; Florent Lyard; Geir Moholdt; Michel Tsamados; Mahmoud El Hajj; Josephine Maton; Jérôme Benveniste; Marco Restano (Polar Science, 2024)

A blood test to monitor bee health across a European network of agricultural sites of different land-use by MALDI BeeTyping mass spectrometry - Dalel Askri; Mathilde Pottier; Karim Arafah; Sébastien N. Voisin; Simon Hodge; Jane C. Stout; Christophe Dominik; Oliver Schweiger; Giovanni Tamburini; Maria Helena Pereira-Peixoto; Alexandra-Maria Klein; Vicente Martínez López; et al. (Science of The Total Environment, 2024)

Passive acoustic monitoring for assessing marine mammals population in European waters: Workshop conclusions and perspectives - Mathilde Michel; Benjamin Guichard; Julie Béesau; Flore Samaran (Marine Policy, 2024)

Phytochemical characterisation and aromatic potential for brewing of wild hops (Humulus lupulus L.) from Northern France: Towards a lead for local hop varieties - Anne-Sophie Paguet; Ali Siah; Gabriel Lefèvre; Mathilde Vandenberghe; David Lutun; Norman Degardin; Jennifer Samaillie; David Mathiron; Charles Dermont; Franck Michels; Marie-Laure Fauconnier; Sylvie Chollet; et al. (Food Chemistry, 2024)

Co-exposure to highly allergenic airborne pollen and fungal spores in Europe - Dorota Myszkowska; Paweł Bogawski; Katarzyna Piotrowicz; Beata Bosiacka; Agnieszka Grinn-Gofroń; Uwe E. Berger; Maira Bonini; Valentina Ceriotti; Athanasios Charalampopoulos; Carmen Galán; Björn Gedda; Nicoleta Ianovici; et al. (Science of The Total Environment, 2023)

An agent-based model to simulate SARS-CoV-2 contamination of surfaces and meat cuts in processing plants - Ngoc-Du Martin Luong; Laurent Guillier; Michel Federighi; Yvonnick Guillois; Pauline Kooh; Anne-Laure Maillard; Mathilde Pivette; Géraldine Boué; Sandra Martin-Latil; Estelle Chaix; Steven Duret (International Journal of Food Microbiology, 2023)

Predictive factors associated with pemetrexed acute toxicity - Mathilde Bonnet; Anne Jouinot; Pascaline Boudou-Rouquette; Vanessa Seif; Clémentine Villeminey; Jennifer Arrondeau; Michel Vidal; Rui Batista; Marie Wislez; Benoit Blanchet; François Goldwasser; Audrey Thomas-Schoemann (European Journal of Clinical Pharmacology, 2023)

Biomarkers of mitochondrial dysfunction and inflammaging in older adults and blood pressure variability - Leonardo Bencivenga; Mathilde Strumia; Yves Rolland; Laurent Martinez; Philippe Cestac; Sophie Guyonnet; Sandrine Andrieu; Angelo Parini; Alexandre Lucas; Bruno Vellas; Philipe De Souto Barreto; Laure Rouch; et al. (GeroScience, 2023)

Preliminary inter-port study of the quality of environments using physiological responses of invertebrates exposed to chronic trace element and organic contamination in Corsica (Mediterranean Sea) - Marion Pillet; Mathilde Dabrowski; Michel Marengo; Lovina Fullgrabe; Michèle Leduc; Quentin Fontaine; Stéphane Le Floch; Valérie Huet; Carine Churlaud; Pierre Lejeune; Hélène Thomas (Ecotoxicology, 2023)

Interoperable vocabulary for marine microbial flow cytometry - Melilotus Thyssen; Gérald Grégori; Véronique Créach; Soumaya Lahbib; Mathilde Dugenne; Hedy M. Aardema; Luis-Felipe Artigas; Bangqin Huang; Aude Barani; Laureen Beaugeard; Amel Bellaaj-Zouari; Alfred Beran; et al. (Frontiers in Marine Science, 2022)
The recent development of biological sensors has extended marine plankton studies from conducting laboratory bench work to in vivo and real-time observations. Flow cytometry (FCM) has shed new light on marine microorganisms since the 1980s through its single-cell approach and robust detection of the smallest cells. FCM records valuable optical properties of light scattering and fluorescence from cells passing in a single file in front of a narrow-collimated light source, recording tens of thousands of cells within a few minutes. Depending on the instrument settings, the sampling strategy, and the automation level, it resolves the spatial and temporal distribution of microbial marine prokaryotes and eukaryotes. Cells are usually classified and grouped on cytograms by experts and are still lacking standards, reducing data sharing capacities. Therefore, the need to make FCM data sets FAIR (Findability, Accessibility, Interoperability, and Reusability of digital assets) is becoming critical. In this paper, we present a consensus vocabulary for the 13 most common marine microbial groups observed with FCM using blue and red-light excitation. The authors designed a common layout on two-dimensional log-transformed cytograms reinforced by a decision tree that facilitates the characterization of groups. The proposed vocabulary aims at standardising data analysis and definitions, to promote harmonisation and comparison of data between users and instruments. This represents a much-needed step towards FAIRification of flow cytometric data collected in various marine environments.

The EMSO Generic Instrument Module (EGIM): Standardized and Interoperable Instrumentation for Ocean Observation - Nadine Lantéri; Henry A. Ruhl; Andrew Gates; Enoc Martínez; Joaquin del Rio Fernandez; Jacopo Aguzzi; Mathilde Cannat; Eric Delory; Davide Embriaco; Robert Huber; Marjolaine Matabos; George Petihakis; et al. (Frontiers in Marine Science, 2022)
The oceans are a fundamental source for climate balance, sustainability of resources and life on Earth, therefore society has a strong and pressing interest in maintaining and, where possible, restoring the health of the marine ecosystems. Effective, integrated ocean observation is key to suggesting actions to reduce anthropogenic impact from coastal to deep-sea environments and address the main challenges of the 21st century, which are summarized in the UN Sustainable Development Goals and Blue Growth strategies. The European Multidisciplinary Seafloor and water column Observatory (EMSO), is a European Research Infrastructure Consortium (ERIC), with the aim of providing long-term observations via fixed-point ocean observatories in key environmental locations across European seas from the Arctic to the Black Sea. These may be supported by ship-based observations and autonomous systems such as gliders. In this paper, we present the EMSO Generic Instrument Module (EGIM), a deployment ready multi-sensor instrumentation module, designed to measure physical, biogeochemical, biological and ecosystem variables consistently, in a range of marine environments, over long periods of time. Here, we describe the system, features, configuration, operation and data management. We demonstrate, through a series of coastal and oceanic pilot experiments that the EGIM is a valuable standard ocean observation module, which can significantly improve the capacity of existing ocean observatories and provides the basis for new observatories. The diverse examples of use included the monitoring of fish activity response upon oceanographic variability, hydrothermal vent fluids and particle dispersion, passive acoustic monitoring of marine mammals and time series of environmental variation in the water column. With the EGIM available to all the EMSO Regional Facilities, EMSO will be reaching a milestone in standardization and interoperability, marking a key capability advancement in addressing issues of sustainability in resource and habitat management of the oceans.

Agricultural exposure and risk of bladder cancer in the AGRIculture and CANcer cohort - Mathilde Boulanger; Séverine Tual; Clémentine Lemarchand; Anne-Valérie Guizard; Michel Velten; Elisabeth Marcotullio; Isabelle Baldi; Bénédicte Clin; Pierre Lebailly (International Archives of Occupational and Environmental Health, 2017)

Lateral Variations of Interplate Coupling along the Mexican Subduction Interface: Relationships with Long-Term Morphology and Fault Zone Mechanical Properties - Baptiste Rousset; Cécile Lasserre; Nadaya Cubas; Shannon Graham; Mathilde Radiguet; Charles DeMets; Anne Socquet; Michel Campillo; Vladimir Kostoglodov; Enrique Cabral-Cano; Nathalie Cotte; Andrea Walpersdorf (Pure and Applied Geophysics, 2016)

Partial sequencing reveals the transposable element composition of Coffea genomes and provides evidence for distinct evolutionary stories - Romain Guyot; Thibaud Darré; Mathilde Dupeyron; Alexandre de Kochko; Serge Hamon; Emmanuel Couturon; Dominique Crouzillat; Michel Rigoreau; Jean-Jacques Rakotomalala; Nathalie E. Raharimalala; Sélastique Doffou Akaffou; Perla Hamon (Molecular Genetics and Genomics, 2016)

CATI: A Large Distributed Infrastructure for the Neuroimaging of Cohorts - Grégory Operto; Marie Chupin; Bénédicte Batrancourt; Marie-Odile Habert; Olivier Colliot; Habib Benali; Cyril Poupon; Catherine Champseix; Christine Delmaire; Sullivan Marie; Denis Rivière; Mélanie Pélégrini-Issac; et al. (Neuroinformatics, 2016)

Characteristics, behaviors and association between Human African Trypanosomiasis and HIV seropositivity among volunteer blood donors in a semi-rural area: A survey from Kikwit, the Democratic Republic of Congo - Lefils Kasiama Ndilu; Mathilde Bothale Ekila; Donald Fundji Mayuma; Alain Musaka; Roger Wumba; Michel Ntetani Aloni (Acta Parasitologica, 2016)
Blood safety is a major element in the strategy to control the HIV epidemic. The aim of this study was to determine the prevalence and the associated factors of a positive HIV test among blood donors and its association between Human African Trypanosomiasis in Kikwit, the Democratic Republic of Congo. A cross-sectional study was conducted between November 2012 and May 2013. An anonymous questionnaire was designed to extract relevant data. The average mean age of participants was 30 years. The majority were man (67.8%). The overall prevalence of HIV, syphilis, hepatitis B, hepatitis C and human African trypanosomiasis was respectively 3.2%, 1.9%, 1.6%, 1.3% and 1.3%. Alcohol intake, casual unprotected sex, not using condoms during casual sex, sex after alcohol intake and seroprevalence of human African trypanosomiasis were significantly associated with a positive HIV test result ( p

Cryptosporidium identification in HIV-Infected Humans. Experience from Kinshasa, the Democratic Republic of Congo - Roger D. Wumba; Josué Zanga; Kennedy M. Mbanzulu; Madone N. Mandina; Aimé K. Kahindo; Michel N. Aloni; Mathilde B. Ekila (Acta Parasitologica, 2015)
Cryptosporidium is an important protozoan parasite affecting HIV/AIDS patients. To determine the prevalence and the species of Cryptosporidium spp by developing a rapid and efficient real-time PCR-RFLP test. A cross-sectional study was conducted among HIV-infected adults from Kinshasa, the Democratic Republic of Congo. Stool specimens were examined by microscopic evaluation and real-time PCR-RFLP. Out of 242 HIV-infected adults, 10 (4.1%) cases of Cryptosporidium were identified by microscopic examination. Using PCR-RFLP, the prevalence of Cryptosporidium spp was 5.4% (n = 13). All the 13 cases of Cryptosporidium spp had the stage of AIDS of HIV infection. Extracted DNA was amplified by nested PCR targeting a 1030-bp fragment of the 18s RNA gene. RFLP analysis identified one C. parvum, four C. hominis and one non determined Cryptosporidium. The capacity to detect C. parvum, C. hominis and non-determined Cryptosporidium was present among our HIV-infected patients.

Annexin A1 in primary tumors promotes melanoma dissemination - Zied Boudhraa; Fabien Rondepierre; Lemlih Ouchchane; Roselyne Kintossou; Anna Trzeciakiewicz; Frederic Franck; Jean Kanitakis; Bruno Labeille; Juliette Joubert-Zakeyh; Bernadette Bouchon; Jean Luc Perrot; Sandrine Mansard; et al. (Clinical & Experimental Metastasis, 2014)

Genetic control of yield and yield components in winter oilseed rape (Brassica napus L.) grown under nitrogen limitation - Anne-Sophie Bouchet; Nathalie Nesi; Christine Bissuel; Michel Bregeon; Amandine Lariepe; Hélène Navier; Nicolas Ribière; Mathilde Orsel; Bruno Grezes-Besset; Michel Renard; Anne Laperche (Euphytica, 2014)
Despite its high nitrogen absorption capacity, oilseed rape (OSR) has a low apparent nitrogen use efficiency (NUE), which makes its production highly dependent on nitrogen fertilization. Improving NUE in OSR is therefore a main target in breeding. The objectives of the present work were to determine the genomic regions (QTLs) associated with yield and to assess their stability under contrasted nitrogen nutrition regimes. One mapping population, AM, was tested in a French location for three growing seasons (2011, 2012 and 2013), under two nitrogen conditions (optimal and low). Eight yield-related traits were scored and nitrogen-responsive traits were calculated. A total of 104 QTLs were detected of which 28 controlled flowering time and 76 were related to yield and yield components. Very few genotype × nitrogen interactions were detected and the QTLs were highly stable between the nitrogen conditions. In contrast, only a few QTLs were stable across the years of the trial, suggesting a strong QTL × year interaction. Finally, eleven critical genomic regions that were stable across nitrogen conditions and/or trial years were identified. One particular region located on the A5 linkage group appears to be a promising candidate for marker assisted selection programs. The different strategies for OSR breeding using the QTLs found in the present study are discussed.

A seafloor experiment to monitor vertical deformation at the Lucky Strike volcano, Mid-Atlantic Ridge - Valérie Ballu; Jérome Ammann; Olivier Pot; Olivier de Viron; Glenn S. Sasagawa; Gilles Reverdin; Marie-Noelle Bouin; Mathilde Cannat; Christine Deplus; Sébastien Deroussi; Marcia Maia; Michel Diament (Journal of Geodesy, 2009)

Impact of carrot resistance on development of the Alternaria leaf blight pathogen (Alternaria dauci) - Cora Boedo; Valérie Le Clerc; Mathilde Briard; Philippe Simoneau; Michel Chevalier; Sonia Georgeault; Pascal Poupard (European Journal of Plant Pathology, 2008)

Both additivity and epistasis control the genetic variation for fruit quality traits in tomato - Mathilde Causse; Jamila Chaïb; Laurent Lecomte; Michel Buret; Frédéric Hospital (Theoretical and Applied Genetics, 2007)

Molecular characterization of a WEE1 gene homologue in tomato (Lycopersicon esculentum Mill.) - Nathalie Gonzalez; Michel Hernould; Frdric Delmas; Frdric Gvaudant; Philippe Duffe; Mathilde Causse; Armand Mouras; Christian Chevalier (Plant Molecular Biology, 2004)

SOX10 mutations in chronic intestinal pseudo-obstruction suggest a complex physiopathological mechanism - Véronique Pingault; Mathilde Girard; Nadège Bondurand; Huw Dorkins; Lionel Van Maldergem; David Mowat; Takashi Shimotake; Ishwar Verma; Clarisse Baumann; Michel Goossens (Human Genetics, 2002)

A fruit-specific phospho enol pyruvate carboxylase is related to rapid growth of tomato fruit - Carine Guillet; Daniel Just; Nathalie Bénard; Agnès Destrac-Irvine; Pierre Baldet; Michel Hernould; Mathilde Causse; Philippe Raymond; Christophe Rothan (Planta, 2002)